Symptom Profile of ADHD in Youth With High-Functioning Autism Spectrum Disorder: A Comparative Study in Psychiatrically Referred Populations. (August 2017) - Joshi, Gagan; Faraone, Stephen V.; Wozniak, Janet; Tarko, Laura; Fried, Ronna; Galdo, Maribel; Furtak, Stephannie L.; Biederman, Joseph
Objective: To compare the clinical presentation of ADHD between youth with autism spectrum disorder (ASD) and ADHD and a sample of youth with ADHD only.Method: A psychiatrically referred sample of autism spectrum disorder (ASD) youth with ADHD attending a specialized ambulatory program for ASD ( n = 107) and a sample of youth with ADHD attending a general child psychiatry ambulatory clinic ( n = 74) were compared.Results: Seventy-six percent of youth with ASD met Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) criteria for ADHD. The clinical presentation of ADHD in youth with ASD was predominantly similar to its typical presentation including age at onset (3.5 ± 1.7 vs. 4.0 ± 1.9; p = .12), distribution of diagnostic subtypes, the qualitative and quantitative symptom profile, and symptom severity. Combined subtype was the most frequent presentation of ADHD in ASD youth.Conclusion: Despite the robust presentation of ADHD, a significant majority of ASD youth with ADHD failed to receive appropriate ADHD treatment (41% vs. 24%; p = .02). A high rate of comorbidity with ADHD was observed in psychiatrically referred youth with ASD, with a clinical presentation typical of the disorder.